Identifying the relationships between subsurface absorber defects and the characteristics of kesterite solar cells - Dae‐Ho Son; Dong‐Hwan Jeon; Dae‐Hwan Kim; Jin‐Kyu Kang; Shi‐Joon Sung; Jaebaek Lee; Taeseon Lee; Enkhjargal Enkhbayar; JunHo Kim; Kee‐Jeong Yang (Carbon Energy, 2023)
Abstract Understanding the defect characteristics that occur near the space‐charge regions (SCRs) of kesterite (CZTSSe) solar cells is important because the recombination loss at the CZTSSe/CdS interface is considered the main cause of their low efficiency. CZTSSe surfaces with different elemental compositions were formed without polishing (C00) and with polishing for 20 s (C20) and 60 s (C60). For C60, a specific region near the SCR was excessively Cu‐rich and Zn‐poor compared to C00 and C20. Various charged defects formed where the elemental variation was large. As the main deep acceptor defect energy level (Ea2) near the SCR increased, the efficiency, open‐circuit voltage deficit, and current density degraded, and this phenomenon was especially rapid for large Ea2 values. As the Ea2 near the SCR became deep, the carrier diffusion length decreased more for the CZTSSe solar cells with a low carrier mobility than for the CuInGaSe2 (CIGSe) solar cells. The large amplitude of the electrostatic potential fluctuation in the CZTSSe solar cells induced a high carrier recombination and a short carrier lifetime. Consequently, the properties of the CZTSSe solar cells were more strongly degraded by defects with deep energy levels near the SCR than those of the CIGSe solar cells.